2017
DOI: 10.1590/s0102-865020170120000006
|View full text |Cite|
|
Sign up to set email alerts
|

Biomechanic and histologic analysis of fibroblastic effects of tendon-to-bone healing by transforming growth factor β1 (TGF-β1) in rotator cuff tears

Abstract: Purpose: To evaluate the effect of transforming growth factor β 1 (TGF-β 1 ) on tendon-to-bone reconstruction of rotator cuff tears. Methods: Seventy-two rat supraspinatus tendons were transected and reconstructed in situ. At 8 and 16 weeks, specimens of three groups; that is control, L-dose (low dose), and H-dose (high dose) were harvested and underwent a biomechanical test to evaluate the maximum load and stiffness values. Histology sections of the tendon-to-bone interface were identified by hematoxylin-eosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…These roles might be affected by the concentration of IL-1β and our study showed IL-1β above 5.19 pg/ml had positive effects. TGF-β1 inhibits MMP-9 and MMP-13 expression to increase collagen accumulation [44] and is known to improve tendon strength and tendon healing [45, 46]. Our study demonstrated that TGF-β1 above 61.79 μg/ml was related to functional improvement in RC tendinopathy.…”
Section: Discussionmentioning
confidence: 53%
“…These roles might be affected by the concentration of IL-1β and our study showed IL-1β above 5.19 pg/ml had positive effects. TGF-β1 inhibits MMP-9 and MMP-13 expression to increase collagen accumulation [44] and is known to improve tendon strength and tendon healing [45, 46]. Our study demonstrated that TGF-β1 above 61.79 μg/ml was related to functional improvement in RC tendinopathy.…”
Section: Discussionmentioning
confidence: 53%
“…TGF-β1 induces differentiation of progenitor cells in tendon, increases collagen III expression and regulates collagen VI, which is important in fibrillogenesis, thereby accelerating tendon reparation processes. These accelerated reparation processes also are connected with higher VEGF expression (8,21,28,30). Some influence on the structure of tendon depends on the biomechanical strength so, knee joint has very interesting signalling pathway during motion -when there are movements in knee joint, then articulatory cartilage squeezes and interstitial fluid from cartilage gets into articulatory cavity.…”
Section: Resultsmentioning
confidence: 99%
“…17 TGF-b1 inhibits matrix metalloproteinase-9 and -13 expression and increases collagen accumulation, improving tendon strength and tendon healing. 1,39 Based on these data, it is possible that higher levels of leukocytes and TGF-b1 in LR-PRP might have better efficacy in RC repair compared with LP-PRP. type III collagen (COL3), scleraxis (SCX), and decorin (DCN) were higher in tenocytes in the PRP groups than in the control group, with LR-PRP higher than LP-PRP.…”
Section: Discussionmentioning
confidence: 99%
“… 17 TGF-β1 inhibits matrix metalloproteinase–9 and -13 expression and increases collagen accumulation, improving tendon strength and tendon healing. 1 , 39 Based on these data, it is possible that higher levels of leukocytes and TGF-β1 in LR-PRP might have better efficacy in RC repair compared with LP-PRP.…”
Section: Discussionmentioning
confidence: 99%